2012
DOI: 10.1177/0886260512455864
|View full text |Cite
|
Sign up to set email alerts
|

Rural Australian Women’s Legal Help Seeking for Intimate Partner Violence

Abstract: Intimate partner violence (IPV) is a widespread, ongoing, and complex global social problem, whose victims continue to be largely women. Women often prefer to rely on friends and family for IPV help, yet when informal support is unavailable they remain hesitant to contact formal services, particularly legal support for many reasons. This study applies a sociological lens by framing the IPV and legal help-seeking experiences of rural Australian women gained from 36 in-depth face-to-face interviews as socially c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Reducing stigma associated with family violence (Ragusa 2013) and improving access to specialist family violence services may increase the likelihood of abused women seeking this type of service and improve the overall success of the intervention.…”
mentioning
confidence: 98%
“…Reducing stigma associated with family violence (Ragusa 2013) and improving access to specialist family violence services may increase the likelihood of abused women seeking this type of service and improve the overall success of the intervention.…”
mentioning
confidence: 98%
“…In such contexts or where victim-survivors or their abusers were well-known, anonymity, privacy, and confidentiality when disclosing violence or accessing support (from friends, support workers, police, court workers or medical professionals) were tenuous at best (Bosch & Bergen, 2006*;George & Harris, 2014*;Lichtenstein & Johnson, 2009*;Loxton et al, 2003*;Neilson & Renou, 2015*;Ragusa, 2013*). This was especially true for women from certain cultural contexts, such as Bangladesh, where family 'honour' is highly prized (Khan, 2015*) or where women occupied leadership roles in their community.…”
Section: Privacy and Shamementioning
confidence: 99%
“…Numerous articles referred to what we have classified as 'abuser allies' (see Bancroft, 2002), where others in a social network offer support for the abuser or their narrative. Consequently, some women found that friends, family, and police would deny, minimise, trivialise or seek to discredit allegations of violence (George & Harris, 2014*;Hornosty & Doherty, 2002*;Mackenzie & Mackay, 2019*;Martz & Saraurer, 2000*;National Rural Crime Network, 2019*;Neilson & Renou, 2015*;Ragusa, 2013*;Wendt et al, 2017*). A victim-survivor in Hornosty and Doherty's (2002*, p. 20) research emphasised that her friends "don't talk about it [abuse].…”
Section: Abuser Allies and Peer Support Networkmentioning
confidence: 99%
See 2 more Smart Citations